Alleviating urban traffic congestion in smart cities - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2018)
Asia's growing incomes have resulted in a booming market in motor vehicles sales. In the past decade, the growth in car sales has been the most rapid in Asia. In 2014, of the 72 million new passenger cars sold worldwide, an estimated 32 million were sold in Asia and 18 million in China. China's vehicle ownership is projected to increase 2.2 times faster than its growth rate for per capita income up to 2030 (Dargay et al, 2007). Urbanisation rates have been correspondingly high in Asia. In 1975, only 17% of China's population lived in cities. In 2010, the figure has risen to 49%, and is projected to increase from 600 million in 2010 to 846 million in 2020, whilst India's urban population is expected to increase from 379 million to 483 million over the same decade.